Interpersonal Skills And Symptoms Of Early Adolescent Depression: A Crosssectional Analysis Of The Role Of Parents - Dewi Nur Anita; Anggriyani Wahyu Pinandari; Siswanto Agus Wilopo (Journal of Social Research, 2025)
The magnitude of the influence of parents on symptoms of early adolescent depression, in this case, it requires active communication between parents who can provide positive emotional encouragement to early adolescents aged 10-14 years. To identify the risk factors for parental interpersonal communication on the early symptoms of early adolescence by considering socio-ecological factors. This cross-sectional study used observational research methods using secondary data from GEAS-Indonesia 2018. The sample of this study included 7th junior high school students aged 10-14 years who met the inclusion and exclusion criteria totaling 3,441 subjects. Calculation of OR value with 95% CI in multivariable analysis using logistic regression. Parent-adolescent interpersonal communication is not significantly related to symptoms, but poor parental communication will have a significant chance of developing symptoms of depression if the adolescent is a female in Denpasar city and has a history of ACEs more than 5 times. The factors associated with adolescents experiencing symptoms of depression were male adolescents [OR: 0.92; 95% CI: 0.98-1.09], adolescents in the city of Bandar Lampung 1.61[OR:1.61; 95% CI:1.33-1.94] and Denpasar 1.60[OR:1.60; 95% CI:1.34-1.91], adolescents with many male friends 1.71[OR: 1.71; 95% CI:1.37-2.13], Adverse Childhood Experiences (ACEs) 3.59[OR:3.59;95%CI: 2.89-4.52] and cases of bullying in adolescents who became victim 1.24 [OR: 1.24;95% CI: 1.05-1.47]. Forming appreciative communication skills for teenagers, especially women in the city of Denpasar, strengthening the Youth Development Group (KBM) program, the "Roots" Program, and the Family Hope Program, especially in the cities of Bandar Lampung and Denpasar